Signifikansi Rumah Adat Baileo Sebagai Simbol Eksistensi Negeri di Ambon - Yulita Titik Sunarimahingsih; Tyas Susanti; Bernadeta Resti Nurhayati (Unika Soegijapranata Semarang, 2020)
Law No. 6 of 2014 concerning villages and the existence of regional autonomy, allows Ambon City to revive the States which are characteristic of the life order of the Ambonese people, with the authority to regulate the lives of its people according to customary law. It can be said that the State, which is in Ambon, is a customary law community unit that has territorial boundaries in one complete cosmic order (physical and metaphysical). The Baileo Traditional House is one of the custom symbols which is quite important in the life order of the indigenous peoples in Ambon City. This paper tries to examine the importance of the Baileo Traditional House as a symbol of the existence of the country. The results obtained from this study show that the role of the Baileo Traditional House is not only as a place associated with traditional processions or events. The Baileo Traditional House has a central role in the order of community life, both basic and related to customary values. The Baileo Traditional House is also the center of the democratic life of indigenous peoples